Expert guidance for COVID-19 vaccine deployment in Switzerland: a Delphi process (Swiss Medical Weekly, 2021)
BACKGROUND AND AIM: Vaccines providing protection against COVID-19 are a core tool for ending the pandemic. Though international organisations created guidance in 2020 for vaccine deployment, this had to be adapted for each country’s situation and values. We aimed to assist public health decision makers by identifying areas of consensus among Swiss experts for the deployment of one or more novel COVID-19 vaccines.METHODS: An electronic, modified Delphi process between September and November 2020. We recruited a convenience sample of experts working in Switzerland from a variety of specialities, who completed two anonymous questionnaires. They voted on clarification questions and guidance statements from 0 (complete disagreement) to 10 (complete agreement). Responses for guidance statements with a median ≥8 and a lower inter-quartile range bound ≥7 were considered as reaching consensus.RESULTS: Sixty-five experts accepted (66% response rate), with 47 completing the first questionnaire (72%), and 48 the second (74%). Statements reaching consensus included: in the first phase we should vaccinate front-line healthcare professionals and people ≥65 years with risk factors; widespread vaccination of children and adolescents should not be an early priority; and vaccines should be provided free of charge in the setting of national or cantonal vaccination campaigns. Statements not reaching consensus included: early vaccination of people living with someone with risk factors who are not themselves at risk; vaccination of people with previous confirmed or suspected COVID-19; and whether vaccination should be mandatory for individuals with certain activities, such as front-line healthcare professionals.CONCLUSIONS: Experts reached consensus on several statements that were available for decision-makers when making key decisions for COVID-19 vaccine deployment in Switzerland. Statements without consensus highlighted areas requiring expert and public dialogue. The modified Delphi process allowed us to rapidly synthesise views from a broad panel of experts on sensitive topics, and could be considered for a broad range of issues during public health crises.